Student teachers’ technological pedagogical content knowledge: assessment in a private school - Daniel S. Fernando; Ana Linda O. Santos; Narlie M. Labanon (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study assessed the technological pedagogical content knowledge (TPACK) among student-teachers in a private school during the academic year 2025-2026. Additionally, it examined the differences in the level of TPACK among the student teachers when grouped by demographics. A quantitative descriptive-comparative research design was employed. The study was participated in by a total of 103 student-teachers. A 47-item adopted instrument was used to collect the data, utilizing a 5-point Likert scale. The descriptive and comparative analyses were employed. Mean, standard deviation, and the Mann-Whitney U test were used. The whole process of this study adhered to the ethical guidelines. Generally, the findings showed that the student teachers obtained high mean scores (M=4.10, SD=0.50) in TPACK. Notably, their technological pedagogical knowledge was rated very high (M=4.31, SD=0.50). Additionally, the results revealed no significant differences (U=380.000, p=0.340) between male and female across all components of TPACK. However, significant differences were observed in pedagogical knowledge (U=881.000, p=0.029) and pedagogical content knowledge (U=903.000, p=0.039) when grouped according to program. The findings imply that the Department of Teacher Education is encouraged to continue to strengthen the integration of technology in pedagogy and content instruction to sustain and further enhance student teachers’ technological competence.